2022
DOI: 10.3390/molecules27061971
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Neuroinflammatory Components from Clausena lenis Drake

Abstract: Clausena lenis Drake (C. lenis) is a folk medicinal herb to treat influenza, colds, bronchitis, and malaria. The 95% and 50% ethanol extract of C. lenis showed significant nitric oxide (NO) inhibition activity in BV-2 microglial cells stimulated by lipopolysaccharide (LPS). Bio-guided isolation of the active extract afforded five new compounds, including a chlorine-containing furoquinoline racemate, (±)-claulenine A (1), an amide alkaloid, claulenine B (2), a prenylated coumarin, claulenin A (3), a furocoumari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…NO production inhibition assay was a useful bioassay for finding anti-inflammatory compounds and extracts [ 40 ]. In this study, it was found that the EtOAc fraction of the ethanol extract and the water extract of T. chinense had significant anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…NO production inhibition assay was a useful bioassay for finding anti-inflammatory compounds and extracts [ 40 ]. In this study, it was found that the EtOAc fraction of the ethanol extract and the water extract of T. chinense had significant anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…1). 1,2 For example, furoerioaustralasine is a natural product isolated from Eriostemon banksii . 3 Dictamnine is a major bioactive component isolated from the root bark of Dictamnus dasycarpus Turcz.…”
Section: Introductionmentioning
confidence: 99%